The Influence of Financial Literacy, Use of QRIS, Length of Business and Working Hours on the Income of Culinary Merchant in Jimbaran - Ambalinggi, Gabriel Patricio; Dewi, Made Heny Urmila (Jurnal Ilmiah Wahana Pendidikan, 2024)
Increasingly tight opposition among traders in an an increasing number of technologically superior generation encourages traders, mainly withinside the culinary sector, to enhance their competencies and skills, including handling commercial enterprise finances, utilising monetary technology, figuring out techniques from enjoy whilst strolling a commercial enterprise to be able to maximize their profits. This studies objectives to research the simultaneous affect of monetary literacy, use of QRIS, period of commercial enterprise and running hours at the profits of culinary in Jimbaran. The forms of records on this studies are quantitative and qualitative. The outcomes of this studies display that monetary literacy, use of QRIS, period of commercial enterprise and running hours concurrently affect the profits of culinary traders in Jimbaran. The outcomes of this studies display that monetary literacy partly has a effective and full-size impact at the profits of culinary traders in Jimbaran. The outcomes of this studies display that traders who use QRIS have better profits than traders who do now no longer use QRIS in Jimbaran. The outcomes of this studies display that the period of commercial enterprise has a effective and full-size impact at the profits of culinary traders in Jimbaran. Working hours don't have any partial impact at the profits of culinary traders in Jimbaran.